Chromatography-mass spectrometric study of Arceuthobium oxicedri raw material - O. I. Panasenko; V. M. Odyntsova; O. M. Denysenko; V. I. Mozul; V. V. Holovkin (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Arceuthobium oxycedri, M. Bieb., commonly known as dwarf mistletoe, is widespread in the Mediterranean region, parasitizing the branches of Juniperus oxycedrus as a host plant. Compared to white mistletoe, it is more aggressive. It exhibits antibacterial, antifungal, phytotoxic, cytotoxic, and insecticidal activities.